Mergers and Efficiency Gains: A Case of Indian Banks - Kumar , Neeraj; Tiwari, Satish Chandra; Choudhary, Pooja (Asian Journal of Empirical Research, 2019)
This paper reflects an attempt to measure the effect of mergers on efficiency of banks in India. Five major merger cases in India during 2000 to 2005 were examined to measure the pre- and post-merger efficiency to achieve the purpose of this study. Secondary data were obtained from bulletins and reports of the Reserve Bank of India (RBI) and Data Envelopment Analysis (DEA) was employed to calculate efficiency. The study found efficiency gains in four merger cases except the merger of the Oriental Bank of Commerce with the Global Trust Bank. The findings of the study suggest that market driven mergers boost and forced mergers lead to a decline in the efficiency of banks.